2006
DOI: 10.1002/j.0022-0337.2006.70.5.tb04112.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Outreach Placement's Effect on Dental Students’ Clinical Confidence

Abstract: This randomized controlled trial compared the effects of outreach placement with traditional, exclusively dental schoolbased clinical experience on students' confidence in providing treatment for patients presenting with common dental problems. Senior dental students (n=49) were allocated at random to existing dental school-based clinics or placement in primary care clinics to work supervised by local dentists. At baseline, students self-rated their global confidence on a five-point scale. These measures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 18 publications
7
62
0
1
Order By: Relevance
“…Outreach placements were seen as essential for students to gain satisfactory clinical experience, and this was evidenced by both the quantitative and qualitative data. This finding is supported by previous studies 18 that also reported that students perceived time spent within outreach primary care centres as enhancing their confidence levels in treating children 23,24 and leaving them feeling better prepared for dental practice. 25 Interestingly, this study revealed that Manchester students, who had the longest periods of time within an outreach setting, did not necessarily have the highest levels of confidence.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Outreach placements were seen as essential for students to gain satisfactory clinical experience, and this was evidenced by both the quantitative and qualitative data. This finding is supported by previous studies 18 that also reported that students perceived time spent within outreach primary care centres as enhancing their confidence levels in treating children 23,24 and leaving them feeling better prepared for dental practice. 25 Interestingly, this study revealed that Manchester students, who had the longest periods of time within an outreach setting, did not necessarily have the highest levels of confidence.…”
Section: Discussionsupporting
confidence: 84%
“…The qualitative data suggested that some students were confused by disparity in clinical opinions between different trainers, which is consistent with previous research. 23,26 Similarly, the COPDEND report expressed concerns over new graduates being guided by DF1 trainers with differing clinical opinions to their hospital-based tutors. 5 It is therefore important that outreach placements are selected carefully and that emphasis is placed on the continuity of teaching between dental school and outreach providers.…”
Section: Discussionmentioning
confidence: 99%
“…There is no outreach programme for the undergraduate oral surgery curriculum in Turkey. The role of outreach and vocational training programmes should be considered in primary care settings to improve and secure students’ confidence in handling clinical procedures …”
Section: Discussionmentioning
confidence: 99%
“…Segundo esses estudos, os estudantes que participaram de processos de formação em que se enfatizam a integração ensino-serviço, demonstram maior consciência da importância dos determinantes sociais no processo saúde-doença 29 e da importância de se compreender o histórico sócioodontológico 30 . Além de adquirirem maior confiança na realização dos mais diversos procedimentos da cínica odontológica 31,32 . Currículos com programas de integração ensino serviço permitem aos estudantes um melhor entendimento das necessidades da comunidade 33 .…”
Section: Discussionunclassified